The New York State Adult Drug Court Evaluation: Policies, Participants and Impacts - Michael Rempel, Dana Fox-Kralstein, Amanda Cissner, Robyn Cohen, Melissa Labriola, Donald Farole, Ann Bader and Michael Magnani (My University, 2016)
This report evaluates adult drug courts in New York State, one of a handful of states that is  engaged in a coordinated effort to institutionalize drug courts statewide. With funding from the Bureau of Justice Assistance of the U.S. Department of Justice, the Center for Court Innovation, in collaboration with the New York State Unified Court System, has spent the past three years documenting the policies, participant characteristics, and performance of participants in eleven of the state’s oldest and largest drug courts. Among other analyses, this report evaluates the impact of six drug courts on recidivism and identifies the participant characteristics and programmatic features that increase the likelihood of successful drug court outcomes.